The characteristic laboratory findings of non-responsiveness to intravenous immunoglobulin in children with Kawasaki disease - Han Gil Cho; Young Kuk Cho; Jae Sook Ma (Korean Pediatric Society, 2010)
Purpose : Although intravenous immunoglobulin (IVIG) treatment is an effective first-line treatment for Kawasaki disease, 10-20% of the patients develop persistent fever or coronary artery complications. Medical records of Kawasaki disease patients were reviewed to assess the characteristic laboratory findings of IVIG nonresponsiveness. Methods : We reviewed the clinical records of 118 children with Kawasaki disease who were treated at the Chonnam National University Hospital from March 2003 to February 2008. The laboratory findings of the IVIG-responder group (n=110) and the IVIG-nonresponder group (n=8) were compared at admission day and at 48 hours and 14 days after IVIG administration. Results : At admission, the level of creatine kinase (CK) was lower (P=0.03) and that of total protein was higher (P< 0.01) in the nonresponders than in the responders. At 48 hours after IVIG administration, the white blood cell (WBC) count (P=0.04) and neutrophil% (P<0.01) was higher in the nonresponders than in the responders. The neutrophil% (P< 0.01) and CK (P=0.01) level at admission was lower than that at 48 hours after IVIG administration in the responders; this decrease was not as apparent in the nonresponders. Conclusion : IVIG nonresponders have lower CK and higher total protein levels at admission and higher WBC count and neutrophil% at 48 hours after IVIG administration. The decrease in the neutrophil% and CK level between at admission and at 48 hours after IVIG administration is remarkably higher in responders than in nonresponders.